Prioritizing Offshore Drilling Waste Strategies Under Zero Total Petroleum Hydrocarbon (TPH) Regulation: an AHP -Based Study at Medco Energi - Susanti, Nuke; Delimunthe, Gallang Perdhana; Prawiraatmadja, Widhyawan (LPPM Universitas PGRI Sumatera Barat, 2025)
The implementation of Indonesia’s Zero Oil Hydrocarbon (TPH) regulation for offshore drilling waste disposal by 2025 presents significant operational and technological challenges for oil and gas companies. This study aims to evaluate and prioritize strategic alternatives that support compliance with the 0% TPH requirement while maintaining operational efficiency and cost-effectiveness. Using a mixed methods approach, this study integrates thematic analysis of stakeholder interviews with quantitative assessment using the Analytical Hierarchy Process (AHP). Five key criteria – environmental compliance, operational efficiency, cost-effectiveness, technology readiness, and regulatory risk mitigation – are used to evaluate four strategic alternatives. Expert judgments from Medco Energi and SKK Migas are synthesized to develop a decision hierarchy. The results indicate that onshore treatment and disposal (30.73%) is the most preferred option, followed by third-party waste management services (26.15%), offshore reinjection (24.49%), and thermal desorption units (18.64%). The implications of this study are that qualified experts in environmental management, offshore drilling, and waste treatment provide input to the AHP model to ensure a robust and multidimensional evaluation. The novelty of this research demonstrates strategies that emphasize infrastructure optimization, stakeholder collaboration, and ESG-based innovation to support regulatory compliance and sustainability in offshore drilling waste management